2021
DOI: 10.17221/445/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrification inhibition and forage productivity of Megathyrsus maximus in Colombian dry tropics

Abstract: Agronomic, nutritional, and environmental aspects are integrated to promote sustainable tropical grassland production. Biological nitrification inhibition (BNI) is a plant-based strategy to improve nitrogen use efficiency by grasses in which they suppress the pace of soil nitrification via exudation of inhibitory compounds. To evaluate the effect of BNI on the productive performance of Megathyrsus maximus under field conditions, we evaluated a collection of 27 germplasm accessions and commercial cultivars of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Similar values for Mulato II and Toledo in monoculture, but lower than the 133.8 cm on average presented for Mombasa, thus indicating a better adaptation of this cultivar to the conditions of the Colombian dry tropics. In the same area of this study, Carvajal-Tapia et al (2021) reported an average height of 130 cm for a collection of 130 accessions of Megatyrsus maximus. Those authors mentioned the good agronomic development of this species under the conditions of the region.…”
Section: Results and Discussion Vigour Height Coverage And Presence O...mentioning
confidence: 85%
“…Similar values for Mulato II and Toledo in monoculture, but lower than the 133.8 cm on average presented for Mombasa, thus indicating a better adaptation of this cultivar to the conditions of the Colombian dry tropics. In the same area of this study, Carvajal-Tapia et al (2021) reported an average height of 130 cm for a collection of 130 accessions of Megatyrsus maximus. Those authors mentioned the good agronomic development of this species under the conditions of the region.…”
Section: Results and Discussion Vigour Height Coverage And Presence O...mentioning
confidence: 85%
“…These were stable and consistently showed good values for all the variables and harvests evaluated. Accession 16062 showed potential for biological nitrification inhibition capacity (Carvajal‐Tapia, Mazabel, et al., 2021) and was classified in the group of accessions with the best nutritional profile in the rainy and dry season (Carvajal‐Tapia, Morales Velasco, et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is adequate for associated pastures (Martínez‐Mamian et al., 2020) and for silvopastoral systems (Barragán‐Hernández & Cajas‐Girón, 2019; Paciullo et al., 2017; Santiago‐Hernández et al., 2016). It exhibits strength, resistance, and persistency under negative edaphoclimatic conditions in the dry tropics, with materials that report adequate nutritional composition (Carvajal‐Tapia, Morales Velasco, et al., 2021), and it shows characteristics of potential biological nitrification inhibition (Carvajal‐Tapia, Mazabel, et al., 2021; Villegas et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Agrosavia Sabanera. This Guinea grass is recognized as one of the best species that improves beef and milk production, especially in tropical countries ( Villegas et al, 2020 ; Carvajal-Tapia et al, 2021 ). In addition, this pasture crop has an excellent nutritional quality and the ability to tolerate adverse abiotic conditions (e.g., drought), being a species of interest for arid regions ( Benabderrahim and Elfalleh, 2021 ).…”
Section: Discussionmentioning
confidence: 99%